Analysis of a Cement Storage bin Considering Lateral Forces using Staad.pro - Antim Jatav; Rahul Sathbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
Concrete has the ability to conform to any desired shape and also it’s economical. Concrete proves to be a very useful material as it offers all the flexibilities in designing and construction of silos and bunkers which are required by any industry and foremost being in the economical limits. Importance of these storage structures has attracted the attention of many researchers worldwide to propose different load calculation methods and design considerations. ACI 1997 is the only available guidelines, for the design of silo and bunkers. In addition to it, different researchers proposed different methods to compute the loads of moving and loading material inside the silos and bunkers. In this study we have comparing two bunkers considering same dimension, capacity and loading condition. In these two cases we are considering concrete and steel material to prepare a comparative study to determine the most suitable type of bunker. The designing and analysis of the structure is done using analytical application Staad.Pro V8i. and results were compared on parameters namely Stress analysis, Support reaction, Deflection Axial Force and Shear Force.